Epoxy-silica/clay nanocomposite for silver-based antibacterial thin coatings: Synthesis and structural characterization - Giraldo Mejía, Hugo Fernando (2017)
Development of new functional coatings in the field of health care, as antibacterial applications, deals with a straight control of the diffusive properties that rules the releasing of the active component. In this work, the development of a silver-rich nanocomposite thin coating, loaded with organically modified clay nanoparticles, is presented. The synthesis process included an environment-friendly silanization process of clay nanoparticles (Laponite® S482) with (3-glycidoxypropyl)trimethoxysilane (GPTMS) and the further hydrolytic condensation with tetraethoxysilane (TEOS). Silanization process and the obtained coatings were analysed by Fourier transformed infrared spectroscopy, UV–visible spectroscopy, X-ray diffraction, thermogravimetric curves and scanning electron microscopy. The silanization process of clay nanoparticles with the organically reactive alkyl alkoxysilane, allowed to stabilize and exfoliate the clay nanosheets within a hybrid organic-inorganic sol-gel material. Ring opening of grafted epoxy groups carried to an increasing of the basal spacing, of intercalated clay nanosheets, from 1.3 to 1.8 nm. Moreover, incorporation of organically modified clay nanosheets introduced a significant stabilization on the development of silver nanoparticles inside the structure of the nanocomposite coating, retaining the silver inside the coating material and restricting the growing of silver nanoparticles on the surface of the coating. Antibacterial behaviour, against E. coli cultures, performed through agar diffusion tests, provided promising results that allow assuming that the studied nanocomposite coating serves as a reservoir of ionic silver, permitting the antibacterial effect.